Two new species of Demicryptochironomus Lenz, 1941 from India with tentative phylogenetic relationship and a revised world key to known males (Diptera: Chironomidae) - Mukherjee, Bindarika; Hazra, Niladri (Zootaxa, 2022)
Demicryptochironomus (s. str.) praeacutus sp. n. and D. (Irmakia) dividuus sp. n. are described based on adult males from India. A revised world key to the known males of the genus and molecular barcodes of both species are provided. A tentative phylogenetic relationship based on morphological characters of adult males of the genus Demicryptochironomus Lenz is also proposed.